Intercropping of lemon grass with poplar (Populus deltoide Bartr. ex Marsh) in Eastern Uttar Pradesh - Raj, Antony Joseph; Lal, S.B.; Daniel, Sameer; Gowda, Vitala (Indian Journal of Agroforestry, 2020)
Experimental field study was conducted at the Forest Nursery and Research Centre, College of Forestry and Environment, Allahabad Agricultural Institute-Deemed University, Allahabad on lemon grass (Cymbopogon flexuosus) under poplar (Populus deltoides) based agroforestry system. The experiment was laid out in open (sole) and shade (under trees) condition with 12 treatments and 3 replications in split plot design. The root slips of lemon grass (Cymbopogon flexuosus) variety 'CKP-25' were planted in three spacing 30 cm x 30 cm, 30 cm x 45 cm and 30 cm x 60 cm and four levels of fertilizer dose viz. N0 P0 K0, N50 P20 K20, N100 P40 K40 and N150 P60 K60 kg/ha were given to the lemon grass. Lemon grass in a spacing of 30x45 cm with the fertilizer application of nitrogen 150, Phosphorus 60 and potassium 60 kg/ha recorded maximum plant height (1.65 m), number of tillers per plant (70), herbage yield (48.5 tons/ha) and oil yield (197.43 kg/ha) under poplar trees.